Changing environments to promote safety in libraries - Ceccato, Vania (European journal of criminology, 2024)
The purpose of this article is to investigate how changes in the environment of a library affect the safety conditions of both visitors and staff. Using principles of Crime Prevention Through Environmental Design, crime and incidents of public disturbance from 2017 to 2020 from libraries in Stockholm, Sweden, are analyzed and later mapped using 3D models in CAD. These findings are inspected via fieldwork visits and then compared with answers from a safety survey with library visitors (N?=?112) and interviews with library personnel (N?=?6). Analysis of variance shows that crime and incidents of public disturbance decrease after these interventions, with clear impacts on their geography. A third of visitors indicate that there have been fewer problems after changes in the library are introduced while staff suggests that training prepares them to manage conflict situations more efficiently. The study concludes with a critical assessment of the methodology and makes suggestions to improve safety conditions in libraries.